2019
DOI: 10.3390/biology8040069
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lipopolysaccharide-Induced Extracellular Vesicles in Cardiac Cell Death

Abstract: Exosomes play a crucial role in the progression of infectious diseases, as exosome release and biogenesis are affected by external factors, such as pathogenic infections. Pyrogens may aide in the progression of diseases by triggering inflammation, endothelial cell injury, and arterial plaque rupture, all of which can lead to acute coronary disease, resulting in cardiac tissue death and the onset of a cardiac event (CE). To better understand the effects of Gram-negative bacterial infections on exosome compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
(56 reference statements)
6
12
0
Order By: Relevance
“…We found that cocaine exposure did not alter the expression of cleaved caspase-9 or -3 ( Figures 3B,C and Supplementary Figures 3B,C ). However, 100 μM cocaine significantly increased histone H2A.x expression ( Figure 3D and Supplementary Figure 3D ), supporting previous findings ( Bell et al, 2019 ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We found that cocaine exposure did not alter the expression of cleaved caspase-9 or -3 ( Figures 3B,C and Supplementary Figures 3B,C ). However, 100 μM cocaine significantly increased histone H2A.x expression ( Figure 3D and Supplementary Figure 3D ), supporting previous findings ( Bell et al, 2019 ).…”
Section: Resultssupporting
confidence: 91%
“…The size and quantity of isolated EVs were measured using NTA and TEM. We found that cocaine did not alter the size of EVs and EVs are visible and easily recognizable ( Figure 1B and Supplementary Figures 1B,D–F ), which ranged from 30 to 150 nm in diameter across conditions, consistent with previous studies ( Bell et al, 2019 ; Crenshaw et al, 2019 ; Jones et al, 2019 ; Kumar et al, 2020 ). However, 100 μM cocaine slightly reduced the number of EV particles per mL compared with the 1 μM cocaine and control conditions, although this difference was not significant ( Figure 1C and Supplementary Figures 1C,D–F ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…After 24 hrs, cells were washed and media was replaced with exosome-depleted media. The experimental flasks were treated with 0.1 μg/mL, 1 μg/mL or 10 μg/mL of LPS for 48 hrs [11]. Following treatment, cell morphology and integrity were visualized and media was collected.…”
Section: Lps Treatment On A549 Cellsmentioning
confidence: 99%
“…14 The recent literature suggests that condition-modified exosomes induce cardiac injury. 15 Macrophage-derived exosomes in patients with diabetes showed proinflammation function, leading to cardiac fibrosis. 16 Meanwhile, exosomes derived from modified macrophages showed a pro-DNA damaging effect, thus leading to senescence.…”
Section: Introductionmentioning
confidence: 99%